Making social capital : case study of two beneficiary communities of the social housing initiative, Lagos, Nigeria - Zgrzywa, Ewa (2009)
Recent estimates have set the world urban population at over 3 billion people. In Nigeria, the massive urban sprawl has resulted in the proliferation of slums that are regarded as areas of extreme poverty. Nevertheless, slum communities possess collective assets in the form of networks and reciprocal relations, yet they often lack capacity to build the type of social capital that could be used for the improvement of their living conditions. Assistance from NGOs and participation in development projects may boost the creation of this resource. The aim of this study is to contribute to the discussion on social capital in urban areas of sub-Saharan Africa. The study examines social capital of two slum communities in Lagos, Nigeria, and the Nigerian Social Housing Initiative (NSHI), project aimed at mobilizing them for the improvement of housing and living conditions. The focus of field research is also on analyzing activities undertaken by the assisting NGO, the Social and Economic Rights Action Center (SERAC), and gaining deeper understanding of factors influencing community social capital. The perspective adopted in this research builds upon the notion of social capital defined by Robert D. Putnam as the membership in networks, social trust and norms of reciprocity that facilitate cooperation. The qualitative case study method employed in this study is rooted in the tradition of the Chicago School of Sociology. The data consists of semi-structured interviews with key informants, participant observation, survey reports, project proposals, newspaper articles, SERAC's publications and booklets of community-based organizations. The findings of this study confirm that slum communities have generally low levels of social capital, however they possess high stocks of bonding social capital, while lacking bridging and linking capital. Historical factors, physical conditions, insecurity of tenure and institutional environment impact the formation and destruction of social capital. The results acknowledge the role of local leaders and the organizational capacity of the poor in bridging between communities and linking with external actors. Additionally, the NGO-led initiatives in the slums need to be carefully planned and implemented to address the lacks in specific components of social capital and utilize opportunities while keeping in mind existing constraints. This study further suggests that internal problems of the NGOs may profoundly impact the success of their social capital initiatives.